Methods of Extracorporeal Immunopharmacotherapy: From General Medical Clinical Practice to Oncologic Practice (Literature Review) - N. Tillyashaikhov, Mirzagoleb; V. Kamishov, Sergey; A. Tillyashaikhova, Mahsuda (International Journal of Psychosocial Rehabilitation, 2020)
The review presents the results of the application of extracorporeal immunopharmacotherapy (EIFT) techniques in medical practice for the treatment of infectious and autoimmune diseases, as well as septic complications. EIFT studies as an accompanying therapy in the treatment of malignant tumors are presented. The widespread practical implementation of EIFT is hindered by inadequate clinical testing for various diseases, a small spectrum of studied drugs, and the lack of adequate methods for predicting efficacy. In our own studies on the example of patients with cervical cancer of the II-III stages, it was shown that the immunotherapy regimen is most effective in complex treatment, including intermittent plasmapheresis followed by EIFT, which improves blood counts, increases leuko- and lymphopoiesis, normalizes cellular and humoral immunity, reduces the main clinical manifestations of chemotherapy toxicity, improves indicators of the subjective state of patients and their quality of life, and also allows you to increase indicators of the five-year survival rate.